Economic and Legal Aspects of the Regulation of Population Migration - Luzina, Tatyana Viktorovna; Ignatova, Irina Viktorovna (Economy of Regions, 2016)
The article is devoted to a current problem of regional development, such as the regulation of labour migration. In the article, the causes of the inefficient use of labour resources are identified and the solutions to reduce tension in the labour market both at the state level and at the level of an individual employee are proposed. The formal rules and informal constraints that have a significant impact on migration are allocated. The institutional support for the regulation of migration in Russia is considered. At the level of the entities of the Russian Federation, the analysis of migration flows for the period from 2012 to 2014 is carried out; the entities of the Russian Federation are grouped according to the degree of the influence of the indicators of the natural movement and the migration of population as well as to the qualification structure of migrants (professional education, age structure). The basic imbalances in the labour market in the entities of the Russian Federation are revealed. The authors have proposed a model for assessing the attractiveness of workplaces based on the objective indicators of the development of Russian regions presented in the statistical report of Federal State Statistics Service. A feature of the model is the ability to determine the main factors influencing the attraction of labour resources to the region. The methodological tools of the research include the mathematical methods of processing statistical data. Testing of the model is conducted for the Federal districts of the Russian Federation. According to the developed model, the coefficient of the attractiveness of a workplace in 2010 and 2014 for all Federal districts of the Russian Federation is calculated. In the article, the legal framework regulating the flow of the human capital is also analysed. The assessment of the implementation of the state program of support for the resettlement in the Russian Federation of compatriots residing abroad is given.